IT Project Manager Competencies and IT Project Success: A Qualitative Study - Che Jusoh, Aliya Nazeera; Nurin Najwa Muhammad Azhar,; Nurul Hidayah Muhamad Sani,; Syahirah Adibah Esa,; Nur Husna Alia Onn,; Nur Aqilah Azizah Nordin,; Saymaharan a/l Mohan,; Diveadarsini a/p A.Jagathison,; Nur Liyana Sulaiman, (Applied Information Technology And Computer Science, 2023)
The competences needed by IT project managers to successfully complete their projects are the subject of this research study. The problem statement and the research background are introduced in the abstract. It claims that the failure of IT projects remains a worry despite ongoing spending and research on IT project management. The primary goal of the study is to determine which competencies are most important for IT project managers. The main conclusions highlight the significance of abilities including communication, project management, team management, business domain expertise, and people skills. In order to improve project success, the abstract's conclusion recommends that IT project managers integrate technical expertise with interpersonal and management abilities.